Accurate numerical solutions of 2-D elastodynamics problems using compact high-order stencils. (March 2020) - Idesman, A.; Dey, B.
Highlights: A new approach for high-order accurate stencils with optimal accuracy. New 25-point stencils for 2-D elastodynamics with 6th order of accuracy. Proof that linear finite elements for elastodynamics have optimal order of accuracy. New approach significantly exceeds accuracy of high-order finite elements. New approach yields accurate results for nearly incompressible materials. Abstract: A new approach for the increase in the order of accuracy of high-order numerical techniques used for 2-D time-dependent elasticity (structural dynamics and wave propagation) has been suggested on uniform square and rectangular meshes. It is based on the optimization of the coefficients of the corresponding semi-discrete stencil equations with respect to the local truncation error. It is shown that the second order of accuracy of the linear finite elements with 9-point stencils is optimal and cannot be improved. However, we have calculated new 9-point stencils with the second order of accuracy that yield more accurate results than those obtained by the linear finite elements. We have also developed new 25-point stencils (similar to those for the quadratic finite and isogeometric elements) with the optimal sixth order of accuracy for the non-diagonal mass matrix and with the optimal fourth order of accuracy for the diagonal mass matrix. The numerical results are in good agreement with the theoretical findings as well as they show a big increase in accuracy of the new stencils compared with those for the high-order finite elements. At the same number of degrees of freedom, the new approach yields significantly more accurate results than those obtained by the high-order (up to the eighth order) finite elements with the non-diagonal mass matrix. The numerical experiments also show that the new approach with 25-point stencils yields very accurate results for nearly incompressible materials with Poisson's ratio 0.4999 .